1977
DOI: 10.1111/j.1476-5381.1977.tb07522.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Gastric Mucosal Damage Induced by Indomethacin and Bile‐salts, and the Actions of Prostaglandins

Abstract: 1 The mechanisms by which the bile salt, sodium taurocholate, potentiates the formation of gastric mucosal erosions induced by indomethacin has been investigated in the rat. 2 Systemic administration of indomethacin lowered resting mucosal blood flow but had no effect on the acid back‐diffusion across the mucosa. 3 Gastric perfusion of taurocholate in acid solution increased acid back‐diffusion and lowered the potential difference. This was accompanied by an increase in mucosal blood flow, which may represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
1
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 260 publications
(81 citation statements)
references
References 17 publications
5
74
1
1
Order By: Relevance
“…The present results clearly confirmed the well-known fact (20,21) that a single topical application of TC to rat stomachs reduced PD followed by increases in luminal pH and GMBF. It has been shown that such GMBF responses in the stomach after damage are mediated by capsaicin-sensitive neurons as well as endogenous prostaglandins (PGs) (22).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The present results clearly confirmed the well-known fact (20,21) that a single topical application of TC to rat stomachs reduced PD followed by increases in luminal pH and GMBF. It has been shown that such GMBF responses in the stomach after damage are mediated by capsaicin-sensitive neurons as well as endogenous prostaglandins (PGs) (22).…”
Section: Discussionsupporting
confidence: 79%
“…Other investigators (1,2) and our group (3) used 5 mM TC in previous studies, but the concentration of TC was increased to 10 mM in this study to ensure the production of the possible dysfunction of capsaicin neurons within a short period. In some experiments, ablation of capsaicin-sensitive neurons was performed by s.c. injection of capsaicin once daily for 3 consecutive days (20,30 and 50 mg/kg) 2 weeks before the experiments (capsaicin pretreatment) (15). Capsaicin injections were given under ether anesthesia, and the rats were pretreated with terbutaline (0.1 mg/kg, i.m.)…”
Section: Tc Treatment and Functional Ablation Of Capsaicin-sensitive mentioning
confidence: 99%
“…In a study on the mechanisms underlying gastric damage in the rat, the increase in acid-back diffusion in the presence of acidified-taurocholate, failed to induce extensive damage, the accompanying rise in mucosal blood flow being thought to prevent acid accumulation within the mucosal tissue (Whittle, 1977). This protective hyperaemic response may be mediated in part by local prostaglandin production since it could be attenuated by concurrent administration of indomethacin (Whittle, 1977), an inhibitor of prostaglandin biosynthesis (Vane, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…This protective hyperaemic response may be mediated in part by local prostaglandin production since it could be attenuated by concurrent administration of indomethacin (Whittle, 1977), an inhibitor of prostaglandin biosynthesis (Vane, 1971). Such a reduction in the prostaglandin-mediated component of hyperaemia would be expected to reduce the ability of the mucosa to dispose of the acid diffusing back into the tissue, leading eventually to acid accumulation, a fall in tissue pH and subsequent necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation